The effects of collocation instruction on high school students’ EFL writing performance : (Trường đại học Cần Thơ, 2018)
The aim of this study is twofold- to investigate the effects of collocation instruction on the complexity, accuracy and fluency of EFL high school students’ writing perform nice and the ways to integrate collocation teaching alongside with traditional vocabulary teaching in high schools. The results are expected to satisfy the hypotheses that collocation teaching will induce greater fluency, complexity, and accuracy in the writing performance among EFL high school students and also contribute to the deeper understanding of the previous studies on the Lexical Approach.